2013 International Conference on Radar 2013
DOI: 10.1109/radar.2013.6651992
|View full text |Cite
|
Sign up to set email alerts
|

A review of high grazing angle sea-clutter

Abstract: This paper reviews the published literature on the characteristics of mono-static radar sea-clutter observed with high grazing angles (typically above about 10°). To date, most of the analysis and modelling of sea-clutter has been undertaken at low grazing angles with the main application being for surface and airborne maritime radars. The paper identifies some of the data sets that have been collected and the empirical models that have been developed from them for the normalised radar crosssection. The amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, the CGNG distributions provide a family of biparametric amplitude distributions with slighter tails than the four classic types of amplitude distributions in sea clutter modelling. In fact, it is found that sea clutter becomes less spiky at medium/high grazing angles [45], which means that the CGNG distributions can provide better goodnessof-the-fit to the sea clutter. This is our motivation to introduce CGNG distributions with Nakagami-distributed textures.…”
Section: Compound-gaussian Model With Nakagami-distributed Texturesmentioning
confidence: 99%
“…Therefore, the CGNG distributions provide a family of biparametric amplitude distributions with slighter tails than the four classic types of amplitude distributions in sea clutter modelling. In fact, it is found that sea clutter becomes less spiky at medium/high grazing angles [45], which means that the CGNG distributions can provide better goodnessof-the-fit to the sea clutter. This is our motivation to introduce CGNG distributions with Nakagami-distributed textures.…”
Section: Compound-gaussian Model With Nakagami-distributed Texturesmentioning
confidence: 99%
“…Statistical changes that occur in the clutter have been described in many publications [16][17][18]. These changes are mathematically represented as a variation of the shape parameter of the model assumed for the clutter.…”
Section: Motivation and Objectivesmentioning
confidence: 99%
“…Several probability distributions with heavy tails have been used to fit sea clutter data. The Weibull (Ping, 2011), LogNormal (Ishii, Sayama, & Mizutani, 2011), K (Chen, Liu, Wu, & Wang, 2013), KK (Watts & Rosenberg, 2013) and WW (Dong, 2006) Weinberg, 2013a). Actually, it has been suggested that this distribution provides better fits that the ones exhibited by the most popular alternatives (Farshchian & Posner, 2010).…”
Section: Introductionmentioning
confidence: 99%